The theoretic basis of logistics: the past and the present - Bakutа Alla (Skhid, 2013)
The role of logistics in decision questions of transformation enterprise’s material-technical security, increase competitiveness enterprises in way lowering costs of sell, retention excessive supply were discovered in the article. The part of logistics in high level organization of production was determined. The correlation between economic effect and scale its widening was defined. The stages of historical progress of logistics, its origin was determined. The definition of notion "logistics" of native and foreign experts was uncovered and own supplement. The schematic classification of possibilities, functions and assignments of logistics as independent kind of business activity was shown on the basis of analysis of publication. The three level of logistic systems accordingly to level of economic activity were defined with record idea of scientists.